2017
DOI: 10.1002/ajh.24735
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of chronic myelomonocytic leukemia treated with hypomethylating agents

Abstract: Hypomethylating agents (HMA) are the most commonly used therapeutic intervention in chronic myelomonocytic leukemia (CMML). Due to the lack of CMML-specific clinical trials, the impact of these agents in the natural history of CMML is not fully understood. We present the largest retrospective series of CMML (n=151) treated with HMA. Mean age at diagnosis was 69 years (range 50–88). According to the CMML-specific prognostic scoring system (CPSS): 17 (15%) were low-risk, 45 (39%) intermediate-1 risk, 42 (36%) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 46 publications
(145 reference statements)
2
32
0
Order By: Relevance
“…Low levels of TRIM33 in CMML patients were due to hypermethylation of the gene promoter and expression could be restored using the hypomethylating agent decitabine. The hypomethylating agents azacitidine and decitabine are commonly used to treat older patients with CMML (Alfonso et al 2017 ) and have recently been shown to confer a significant survival advantage to CMML patients in the first year after diagnosis (Zeidan et al 2017 ). Future studies are warranted to investigate whether TRIM33 could be used as a biomarker of response to these agents in CMML.…”
Section: Trim33mentioning
confidence: 99%
“…Low levels of TRIM33 in CMML patients were due to hypermethylation of the gene promoter and expression could be restored using the hypomethylating agent decitabine. The hypomethylating agents azacitidine and decitabine are commonly used to treat older patients with CMML (Alfonso et al 2017 ) and have recently been shown to confer a significant survival advantage to CMML patients in the first year after diagnosis (Zeidan et al 2017 ). Future studies are warranted to investigate whether TRIM33 could be used as a biomarker of response to these agents in CMML.…”
Section: Trim33mentioning
confidence: 99%
“…Their mechanism of action also remains unclear, but do not rely on clonal eradication [9]. Finally, outcome after failure of HMA in CMML, when half of patients have progressed to AML, remains very difficult, with overall survival of ~6 months [70]. Newer treatment options are thus needed in CMML.…”
Section: Treatmentmentioning
confidence: 99%
“…The hypomethylating agents (HMA) azacitidine (AZA) and decitabine (DAC) seem active in CMML, though they have mostly been explored retrospectively [69,70], reporting overall response rates in the 40-70% range. In retrospective studies controlling for biases, there does seem to be a significant difference between DAC and AZA in this population (Duchmann et al, manuscript in preparation), even though several authors have suggested that DAC could be beneficial in proliferative CMML [70,71], possibly because standard regimens of DAC are slightly more myelotoxic than AZA regimens. HMA also seem active in patients with extra-medullary disease [71].…”
Section: Treatmentmentioning
confidence: 99%
“…However, internationally validated treatment algorithms for CMML are still lacking, and treatment remains loosely codified. The hypomethylating agents (HMA) azacitidine (AZA) and DAC seem active in CMML, though they have mostly been explored retrospectively, reporting overall response rates in the 40–70% range [ 10 , 11 ]. For this case, the management of cytopenias is similar to that for MDS based on the MDS-like features and had a good response for DAC.…”
Section: Discussionmentioning
confidence: 99%